Professionalization and anguish: some reflections on suicide in Universities (Research, Society and Development, 2021)
This text aims to discuss and reflect on issues related to suicide in the spaces of Brazilian universities. The methodology used consisted of a review of articles available online, statistical data released by the World Health Organization, as well as information on productions contained in the Capes Journal database. The explanation sought to present reflections on philosophical, sociological and psychological aspects relevant to the situation of suicide, which characterizes it as an event with multifactorial causes. In addition, insertions were made about the requirements established in the context of the university, as well as the relative influence of the internet as a possible start trigger for the execution of the suicidal act in adolescents. It is hoped that the text presented can serve as a reflection and stimulus for discussions about suicide in all social spaces, in order to create, from this, the perspective of developing preventive actions with the aim of valuing and preserving life.